The Existence of Women's Entrepreneurship in the VUCA Era: Analyzing The Role of Socio-Cultural Support System and Financing on MSMEs - Yerisma Welly; Musa Fernando Silaen; Debi Eka Putri; Martin Yehezkiel Sianipar (Yayasan Ilomata, 2023)
The challenge for MSMEs in the digital era is the emergence of Volatility, Uncertainty, Complexity, and Ambiguity or VUCA, so that the role of socio-cultural support systems and relevant financing is needed for MSMEs, especially those based on women's entrepreneurship. This study aims to analyze how the role of the socio-cultural support system and financing in the development of women entrepreneurship-based MSMEs. This research is quantitative with survey method. Research data were collected through interviews; focus group discussions (FGDs); and surveys of respondents of women entrepreneurship-based MSMEs. Based on the research results, it is known that women entrepreneurship MSMEs can face the VUCA era through the role of the socio-cultural support system, especially dimension_a and dimension_b in developing their business. Then, there is also the role of the financing support system, namely dimension_a and dimension_b. The existence of MSME development supported by the role of the socio-cultural support system and financing will improve the economic conditions of MSME actors in a sustainable manner, even in the VUCA era.